Chemical composition of the crinoid skeletal remains (Echinodermata) in weathered limestones of the Bohemian Lower Devonian (Barrandian area) - Petr,V.; Prokop,R.J.; Mihaljevic,M.; Sebek,O. (Journal of the Czech Geological Society, 1997)
The authors give a brief report on the chemical composition of Lower Devonian crinoid skeletal remains and a preliminary interpretation of it. An enormous body of isolated crinoid ossicles from various localities of the Barrandian ”white beds” was collected and 40 samples were prepared for chemical analysis. It was proved that the fossil crinoid ossicles are uniformly low-Mg calcite regardless their stratigraphical position or regional geological condition. In the samples the Fe, Pb, Zn, Cu, Mn, Sr, Li, Na, K, MgO, CaO contents and the insoluble residue were established. A simple evaluation of modern anthropogenic contamination by heavy metals was made using samples derived by previous investigators at the same localities. The possible progressive pollution with heavy metals in relation to the beginning of this century was confirmed in no sample (some samples show even a slight decrease in the heavy metal concentrations) In each sample independent measurements of element contents were recorded for the skeletal ossicles of the crinoid pelma (esp. columnals) as well as of the crown (esp. brachials). The differences between trace element contents in pelma and crown of the crinoids turned to be too large that they cannot be caused by analytical error. The latter observation had verified that some parts of the living Palaeozoic crinoid body had accumulated certain trace metals. Results of the analyses convincingly demonstrated that the Barrandian crinoids exhibited biomagnification of certain elements and were probably very important in the cycling of trace metals in the sea Finally 12 stable isotopic samples (40 measurements), were analyzed, including crinoid brachials, crinoid columnals, brachiopod shells and samples of the rock. No palaeotemperature records were established. From our results it seems that an alteration of the original isotopic signal in a diagenetic environment open to meteoric water could explain the relatively low δ18O and high δ13C (related to the PDB standard) However the geochemical as well as the stable isotopic interpretations are only preliminary and left open to question.